Model Pemberdayaan Masyarakat Adat dalam Menghadapi Perubahan Sosial di Kabupaten Pegunungan Arfak Provinsi Papua Barat - Krisnawati Krisnawati (Indo Publishing, 2026)
This paper aims to construct a model of indigenous community empowerment in responding to social change in the Arfak Mountains. Social transformation driven by development expansion, market economic integration, and shifts in values and social relations has affected local livelihoods, customary institutional structures, and cultural practices. This research employs a qualitative approach using ethnographic methods to gain an in-depth understanding of lived experiences, symbolic meanings, and community adaptation strategies in navigating these dynamics. Data were collected through participant observation, in-depth interviews with customary leaders, women, and youth, as well as the review of local documents. The data were analyzed interpretatively through processes of reduction, categorization, and meaning-making. The findings indicate that effective empowerment is contextual, participatory, and rooted in local wisdom. The proposed model emphasizes strengthening customary institutions, community-based resource management, sustainable local economic development, and the creation of dialogue spaces between customary actors and government. Empowerment is understood not merely as economic capacity building, but as a collective process that reinforces cultural identity, social solidarity, and community resilience to change. This study offers an ethnography-based empowerment framework that is sensitive to the values and social structures of indigenous communities in the Arfak Mountains.